Techniques of Microalga Culture Nannochloropsis oculata as a Natural Feed Source - Wahju Tjahjaningsih; Anggraini Widihastuti; Bagus Satria; Ratna Yulianti (Airlangga University, 2022)
Nannochloropsis oculata is a microalgae that acts as a natural food source in fisheries. The need for N. oculata can be met through progressive culture starting from laboratory scale culture to provide inoculant stock to mass culture using concrete tubs. The culture of N. oculata begins with the preparation and sterilization of culture media and equipment, fertilizer production, microalgae culture starting from the laboratory scale, intermediate scale, and mass scale, observing the density of microalgae and water quality. The lag phase of N. oculata occurs on the first and second days, the exponential growth phase lasts for four days, followed by a stationary phase that occurs on the seventh day. Peak population density of N. oculata on all culture scales occurred on day 6 with culture density in glass containers 14.58x106 cells/mL, carboy culture 11.6x106 cells/mL, intermediate culture 5.1x106 cells/mL, and mass culture 9.85 x106 cells/mL. The growth rate of microalgae N. oculata from the beginning of growth to day 6 was highest on the intermediate scale. The size of the container and the different composition of fertilizer at each culture scale caused differences in the peak population density and growth rate of N. oculata. Production of N. oculata can be carried out in bulk while still paying attention to every stage of culture preparation and microalgae culture activities as a standard operating procedure for microalgae culture to prevent contamination. Keywords: progressive culture, microalgae, Nannochloropsis oculata